2013
DOI: 10.3389/fgene.2013.00141
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between two FISH techniques in the in vitro study of cytogenetic markers for low-dose X-ray exposure in human primary fibroblasts

Abstract: This work is about the setup of an in vitro system to report low-dose of X-rays as measured as cytogenetic damage. Q- and multicolor FISH (m-FISH), for telomere length and chromosome instability analysis, respectively, were compared to evaluate their sensitivity in the low-dose range in human primary fibroblasts. No telomere length modulation was observed up to 1 Gy in cycling fibroblasts, though reported for high doses, by that frustrating the purpose of using it as a low-exposure marker. To date the m-FISH i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…As γ -H2AX represents a biomarker of the DSB, but not a functional component of the DDR, 2 , 3 , 4 we further analyzed DSBS sensing using 53BP1, a protein that accumulates within PML-NBs and is involved in DSBs repair. 41 , 42 The time-course analysis of 53BP1 recruitment at the DSBs in in vitro and in vivo models of APL indicated that the disruption of the PML-NBs slows its recruitment at the DSBs after IR. 53BP1 was nonrandomly associated with PML-NBs and its distribution within the nucleus was dependent on PML-NBs integrity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As γ -H2AX represents a biomarker of the DSB, but not a functional component of the DDR, 2 , 3 , 4 we further analyzed DSBS sensing using 53BP1, a protein that accumulates within PML-NBs and is involved in DSBs repair. 41 , 42 The time-course analysis of 53BP1 recruitment at the DSBs in in vitro and in vivo models of APL indicated that the disruption of the PML-NBs slows its recruitment at the DSBs after IR. 53BP1 was nonrandomly associated with PML-NBs and its distribution within the nucleus was dependent on PML-NBs integrity.…”
Section: Discussionmentioning
confidence: 99%
“…The mFISH was performed by hybridizing chromosome spreads with the 21 × mFISH Probe Kit (MetaSystems, Altlussheim, Germany) as described elsewhere. 41 Karyotyping and cytogenetic analysis of each single chromosome was performed by the ISIS software (MetaSystems, Altlussheim, Germany). Detailed procedures are in Supplementary Materials and Methods .…”
Section: Methodsmentioning
confidence: 99%
“…Based on these findings, for a biodosimetry purpose, it is possible that biodosimetry using painting of all chromosomes (multicolor FISH) is better than with painting only several chromosomes. Multicolor FISH is also considered as the best method for assessment of a chromosome's structural damage because it allows unstable and stable aberrations to be detected [25].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the M-FISH technique has been shown to be a powerful tool for detailed analyses of translocations and CCAs in the whole genome at very low to high doses of IR exposure, as it allows all chromosomal homolog pairs to be differentiated ( 32 , 33 ). It was shown to be sensitive enough to detect translocations and other CAs at doses as low as 0.1 Gy of low LET IR ( 34 ). Though the long-term stability of translocations and the usefulness of this technique was recently validated ( 35 ), M-FISH analysis is laborious, time consuming (~5 days to obtain results), and expensive; standardization and automation will be key to improving the practical significance of FISH-based translocation assays.…”
Section: Discussionmentioning
confidence: 99%